The depth of the facial nerve in the mastoid bone - Kumar, B. Y. Praveen; Chandrashekhar, K. T.; Veena Pani, M. K.; K. C., Sunil; S., Anand Kumar; ., Thanzeemunisa; Leivang, Vanlalhriati (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The hallmark of the temporal bone is variation. Various important structures like the facial nerve run in the temporal bone at various depths which can be injured during mastoidectomy. Methods: Twenty wet cadaveric temporal bones were dissected. A cortical mastoidectomy was performed followed by a canal wall down mastoidectomy and the depth of the vertical segment of the facial nerve in the mastoid was determined. Results: The mean depth of the second genu was 13.82 mm. The mean depth of the stylomastoid foramen was 12.75 mm and the mean distance from the annulus at 6’0 clock to the stylomastoid foramen was 10.22 mm. Conclusions: There is significant variation in the average depth of the facial nerve in the mastoid.